A new species of Tenothrips pollinating Dipterocarpus sublamellatus in Malaysia - Ng, Y.f.; Ain, N.; Lau, K.h. (Zootaxa, 2019)
Tenothrips keruing sp. n. is described from Malaysia. This new species was taken from the flowers of Dipterocarpus sublamellatus (local name Keruing kerut) during the recent mass-flowering. The male of this species has a pair of stout setae on abdominal tergite IX, and there are no sternal pore plates. A key to species of Tenothrips from Indomalaysia is provided.